The Relationship of Vitamin D Insufficiency with Low-Energy Fractures in Children - Alosaimi, Majed Nasser; Qari, Yousef Hussni; Alnasr, Abdulaziz Abdulelah Abu; Barnawi, Hani Ibrahim; Bazaid, Abdullaziz Mohammad; Alotaibi, Khalid Ayidh; Khan , Muhammad Anwar (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Approximately 50% of the world population are suffering from Vitamin D insufficiency. Vitamin D is one of the steroid hormones, which is a fat soluble vitamin that has a critical role in maintaining the homeostasis of bones. Low-energy fractures are defined as falling from the level of standing height or even less that usually should not result in fractures. Another study that was done in Jeddah on a sample of 510 children between the age of 4–15 taken in the pediatric clinic at Jeddah Clinic Hospital-Kandarah. 59% had relative deficiency, and 27% had a deficiency in 25-hydroxyvitamin D. AIM: Therefore, this research is conducted to collect more evidences to assess the association between vitamin D level and low-energy fractures in children. METHODS: The study group consisted of 14 children aged 3–15 years old with low-energy fractures and the control group consisted of 24 children in the same age without fractures. Vitamin D level was measured in each one of them and X-ray was obtained from the cases to prove the presence of low-energy fracture. The analysis plan that was used in this research is Fisher’s exact test to overcome the small sample size. RESULTS: Vitamin D levels were found deficient in four cases, and eight of them were insufficient. Whereas, the normal level of Vitamin D was found in only two of the cases. On the other hand, in the control group the level of Vitamin D was deficient in four participants, and 15 others were found to be insufficient. Also, five of the participants were found to have a normal Vitamin D level. According to the results, low levels of Vitamin D were observed in both groups. A total of 23 out of 38 children enrolled in the study were found to have an insufficient Vitamin D level. The result of p = 0.718 which is not significant to prove the correlation between Vitamin D insufficiency and low-energy fractures. CONCLUSION: In conclusion, this study did not show any relation between Vitamin D level and the presence of low energy fracture. Future studies are required to include more subjects and centers to their study or to compare the low energy fracture and high energy fracture in term of Vitamin D level.